The Effects of Paternity Leave on Fertility and Labor Market Outcomes - Lídia Farré; Libertad González Luna (Institute of Labor Economics (IZA), 2017)
This paper studies the effects of a father quota in the parental leave period on households' labor market and fertility decisions. Identification is based on the 2007 reform of the Spanish family benefit system, which extended the sixteen weeks of paid parental leave by two additional weeks exclusively reserved for fathers and non-transferable to mothers. Using a regression discontinuity design, we show that the reform substantially increased the take-up rate of fathers (by as much as 400%), as well as the re-employment probability of mothers shortly after childbirth (by about 11%). However, it did not affect parents' longer-term leave-taking or employment behavior. We also find that the introduction of the two weeks of paternity leave delayed higher-order births and reduced subsequent fertility among older women (by about 15%). These results suggest a limited scope for the father quota to alter household behaviors beyond the parental leave period and reduce gender inequality at the workplace.
Keywords: J48; J13; J16; 330; natural experiment; paternity leave; fertility; labor market and gender